Preoperative preparation of patients for aortic aneurysm surgery - Yu. V. Belov; R. N. Komarov; I. A. Vinokurov (Сеченовский вестник, 2014)
The paper presents the current practical knowledge of the pathogenesis of postoperative complications in aortic surgery. Recommendations on the tactics of treating patients and on their preoperative preparation are given in this article.